STRATEGI PENGEMBANGAN USAHA AGROINDUSTRI KUE BAWANG DI DESA PASIR UTAMA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Maskuri, Jati (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Agro-industrial development will increase demand for agricultural products so as to increase production, the price of agricultural output and farmers income. The purpose of this research to determine the magnitude of costs, revenues, profits, and identify strengths, weaknesses, opportunities, threats and formulating alternative development strategies that can be applied in the development of agro-industry in Desa Pasir Utama onion cake. Sampling method used is purposive sampling. Analysis of the data used is the analysis of business development, IFE and EFE matrix, SWOT and QSPM. The research concludes that the period 3 June to 3 July 2015 Mr Nawawi agro-business revenues of Rp 7.3152 million,-. Strategic priorities is to increase the amount of production to keep pace with growth and take a business opportunity that is wide and cooperate with the government obtained a total of 5,501 fascination.